Bio-sorption of Chromium using Aquatic Plant, Lepironia Articulata - Abdul Syukor, Abd Razak; Zularisam, A. W.; M. I. M., Said; S., Sulaiman; Siddique, Md. Nurul Islam (AENSI, 2015)
This work was focused at investigating the improvement of the heavy metal removal process produced by the aquatic plant, Lepironia articulata for the treatment of wastewater. The bio-sorption of chromium (Cr) by the aquatic plant, Lepironia articulata signifies one of the key alternatives for heavy metal removal. The application of Lepironia articulate as bio-absorber of heavy metal hasn’t been studied yet. The bio-sorption of chromium (Cr) by the aquatic plant, Lepironia articulata near to Taman Anggerik, Kedah, Malaysia, was examined in wastewater contaminated with 4, 8, 12 and 16 mg l -1 of Cr. chromium concentrations were analysed in the wastewater regularly and in aquatic plant biomass after the experiments. The results revealed that maintaining pH at 6.1 ± 0.1, temperature at 22 ± 1 ºC and photoperiod at 12 h/j Lepironia articulata was capable of accumulating in its biomass 3, 15, 24 and 25 mg g -1 DM, for the four preliminary Cr concentrations selected. At the selected Cr concentrations, the heavy metal removal ranged between 62.45– 72.84%. The mass balance analysis carried out during the experiment revealed that approximately 40–63% of Cr (based on the preliminary Cr concentrations in wastewater) was eliminated through precipitation process. Thus, bio-sorption of Cr using aquatic plant, Lepironia articulata may bring a major point of improvement of the conventional wastewater treatment process.